The carbon footprint associated with the overuse of short-acting β2-agonists in asthma patients - Chao-Hsien Chen; I-Chih Lin; Chih-Cheng Lai; Hsing-hui Liu; Ya-Hui Wang; Cheng-Yi Wang; Hao-Chien Wang (Environmental Research Communications)
Background . In recent years, greenhouse gas (GHG) emissions from inhalers have received more attention. The inhalers are classified as controllers and relievers, which are mainly short-acting beta-agonists (SABA), and SABAs account for more than 50% of all inhaler use in most countries. The overuse of SABA is common in asthma patients, but the environmental impact related to these patients has not yet been studied. Methods . Asthma patients were retrieved from Taiwan’s National Health Insurance Database between 2011 and 2020. These patients were classified as SABA overuse (≥3 canisters annually) and controlled (<3 canisters annually) according to the 12-month baseline period, and the GHG emission in the following year was calculated. The propensity score matching (PSM) was used to balance patients in two groups. Results . A total of 243,136 asthma patients were included for analysis. The annual mean GHG emission associated with the use of inhalers was 69.90 kg/person/year carbon dioxide equivalent in the SABA overuse group. After PSM, there were 22,605 patients in each group, and the mean GHG emission was 2.85 times higher in the SABA overuse group compared to the control group, which was due to both the increased use of SABAs and controller inhalers. Conclusion . The asthma patients who overused SABAs had a greater environmental impact compared to those with acceptable SABA use. It is essential to consider environmental implications when developing asthma treatments, and further research is needed on how to decrease the amount of GHG emissions from inhalers.